The Hierarchy of Protoxylem Groupings in Primary Root and Their Plasticity to Nitrogen Addition in Three Tree Species - Li, Zhongyue; Wang, Siyuan; Wang, Wenna; Gu, Jiacun; Wang, Yan (Frontiers in Plant Science, 2022)
Protoxylem grouping (PG), a classification based on the number of protoxylem poles, is a crucial indicator related to other functional traits in fine roots, affecting growth and survival of individual root. However, within root system, less is known about the arrangement of PG. Moreover, the responses of PG to fertilization are still unclear. Here, we selected three common hardwood species in Northeast China, Juglans mandshurica, Fraxinus mandshurica and Phellodendron amurense, conducted root pruning and nutrient addition. In this study, we analyzed the PG, morphology and other anatomy traits of newly formed root branches. The results showed all root length, diameter and stele, as well as hydraulic conductivity were significantly positive related to the PG number, and the PG number generally decreased with ascending root developmental order, these patterns were independent of species and fertilization. Additionally, we also found the plasticity of PGs to environmental changes, in term of the increased frequency of high PG roots after fertilization, significantly in J. mandshurica and F. mandshurica. Therefore, the heterogeneity, hierarchy and plasticity of individual roots within root system may be widespread in woody plants, which is of great significance to deepen our understanding in root growth and development, as well as the belowground ecological process.